Attenuation assessment of medical protective eyewear: the AVEN experience. (28th April 2016) - Bertolini, M; Benecchi, G; Amici, M; Piola, A; Piccagli, V; Giordano, C; Nocetti, L
Abstract: The goal of this paper is to test the attenuation capability of seven models of protective eyewear used in routine clinical practice. Scattered radiation from a standard patient was simulated by using a water tank located over the treatment couch of a GE Innova 3100 x-ray angiography system. Seven protective eyewear models were tested using an anthropomorphic phantom mimicking the first operator. At each test, 4 thermoluminiscent dosimeters were placed on the phantom (respectively in front of the protective eyewear, under the eyewear, on the left earpiece and at chest level) in order to have an eyewear-independent reference. A test session without glasses was also acquired. Each model was tested with standard posterior–anterior (PA) projections and the two most common protective eyewear were tested using LAO90° and LAO45°CRA30° projections. A worst-case scenario was created to be sure of having an upper limit for the assessment of eyewear attenuation in routine clinical practice. In PA projections, the absolute attenuation value ranged between 71% and 81%, while relative attenuation between dose measured at eye lens and that measured at eyewear earpiece ranged from 67% to 85%. The slightly wider range was probably due to scatter radiation variability; anyway, differences are still included in the variable uncertainty of experimental measurements. It is worth noting that #3 eyewear model (the one without lateral protection) allows an attenuation similar to that of #5 eyewear model (with 0.5 mm lead lateral protection) in LAO90° and LAO45°CRA30° projections. Despite the experimental limitations, a description of the radiation properties of protective eyewear concerning radiation attenuation can be useful to rely on protection devices which can be used in routine clinical practice.